Effect of forest habitat on the distribution of lichen species in şerif yüksel research forest (Bolu, Turkey) - (:unkn) unknown (Pakistan Botanical Society, 2016)
The paper presents the results of a study evaluating impact of habitat factors on distribution of lichen species in a forest ecosystem, in Şerif Yüksel Research Forest (Bolu-Turkey), by applying “binary logistic regression” as the main analysis tool. The variables used for logistic regression were tree species, forest purity, altitude, slope, aspect, tree diameter and number of lichen species. Since it may only be possible to be installed within the model when the number of surveillance of the species is more than 20 in the study area. Distribution of 42 of the 82 epiphytic lichen species were modeled by logistic regression. It is concluded that among these variables, "number of lichen species" and "to be a mixed forest" were the most appropriate variables used in the models. In conclusion, binary logistic regression model can be successfully used in lichen species distribution in forest habitat. © 2016, Pakistan Botanical Society. All rights reserved.
Keywords: Binary logistic models; Forest habitat; Lichen distribution models; Present-absent data